Smart grid projects in Europe: Current status, maturity and future scenarios. (15th August 2015) - Colak, Ilhami; Fulli, Gianluca; Sagiroglu, Seref; Yesilbudak, Mehmet; Covrig, Catalin-Felix
Highlights: This study is grounded on the smart grid database of the JRC (European Commission). The European smart grid projects are analyzed in many respects. The Western part is already transitioning to a D&D phase in specific sectors. The Eastern part lags behind in terms of smart grid initiatives and investments. Short-term future scenarios are created by using time series forecasting models. Abstract: The attention on the smart grids and smart grid technologies has grown significantly over the last few years. The analysis made in this study is grounded on the smart grid projects database of the Joint Research Centre (European Commission). The European smart grid projects are analyzed among others in terms of: number, countries, duration and collaboration. Additionally, an analysis is done regarding the annual number of starting and concluded/planned to be concluded projects, the total number of participants per year, the distribution of smart grid applications per stage of development, year and EU country and an overview of the investments in the European smart grid projects is provided. Afterwards a forecast is done regarding the number of projects. As a result of graphical and predictive analyses, many essential inferences are achieved related to the current status and the anticipated short-term trends of smart grid projects.